2018
DOI: 10.21660/2018.47.06109
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Liquid Smoke Produced From Palm Kernel Shells Pyrolysis as a Natural Preservative in Fish Balls

Abstract: This study investigated the utilization of liquid smoke as a natural preservative in fish balls without reducing their nutrition and aesthetic value. The liquid smoke used in this research was obtained through pyrolysis of palm kernel shells at temperatures of 340, 360, and 380°C. The resulting liquid smoke was then purified using a two-stage distillation process at a temperature of 200°C in order to remove unwanted compounds. This grade-1 liquid smoke was then used to preserve fish balls. The parameters asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 21 publications
(18 reference statements)
0
27
0
2
Order By: Relevance
“…% and acetic acid=3.40 wt. %) 1 , which maintained the freshness of the fish 16,19 . For comparison, fish samples that did not receive liquid smoke treatment turned a cream color after only 8 hours.…”
Section: Organoleptic Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…% and acetic acid=3.40 wt. %) 1 , which maintained the freshness of the fish 16,19 . For comparison, fish samples that did not receive liquid smoke treatment turned a cream color after only 8 hours.…”
Section: Organoleptic Testsmentioning
confidence: 99%
“…In addition, liquid smoke can contribute a unique flavor, taste and color to foods. Several researchers have studied the effects of liquid smoke produced from palm kernel shells to preserve mackerel 16 , fish ball 18 and tofu 19 . However, to our knowledge, there is no research reported on the utilization of durian peel biomass as a natural preservative, despite the wide availability and potential usefulness of durian peel waste.…”
Section: Introductionmentioning
confidence: 99%
“…A food product that has high nutritional value, good flavor and good taste will have little interest from customers if the product does not also have an attractive color. Fish soaked in 0.5-3% liquid smoke produced at 380°C had the most optimum results, probabaly due to a high content of phenol and acetic acid, which maintained the freshness of the fish 16,19 . For comparison, fish samples that did not receive liquid smoke treatment turned a cream color after only 8 hours.…”
Section: Organoleptic Testsmentioning
confidence: 99%
“…In addition, liquid smoke can contribute a unique flavor, taste and color to foods. Several researchers have studied the effects of liquid smoke produced from palm kernel shells to preserve mackerel 16 , fish ball 18 and tofu 19 . However, to our knowledge, there is no research reported on the utilization of durian peel biomass as a natural preservative, despite the wide availability and potential usefulness of durian peel waste.…”
mentioning
confidence: 99%
“…Senyawa asap cair ini mengandung senyawa-senyawa yang berfungsi sebagai antibakteri, anti jamur dan senyawa antioksidan [1,2,4,20,21], sehingga dapat menjadi bahan alami dalam pengawetan makanan. Beberapa penelitian sebelumnya menunjukkan bahwa asap cair dapat digunakan untuk mengawetkan tahu [10], bakso dan ikan [7,13].…”
Section: Teoriunclassified